Аналіз критеріїв, що впливають на вибір автозаправного комплексу - Карпій, О. П.; Васильців, Н. М.; Михайлик, Н. І. (Видавництво Львівської політехніки, 2016)
Розглянуто основні критерії, які впливають на вибір водієм автозаправної станції. Подано детальну структуру автозаправного ринку України. Проаналізовано залежність якості палива від джерела його походження. Розглянуто ціну палива, зокрема у Львівській області. Подано кількісне розташування автозаправних станцій по усіх областях України та структуру послуг, пропонованих автозаправними комплексами. In the article the basic criteria that influence the driver`s choice of the petrol station are considered. The main criteria, that drivers give maximum evaluation to, are: the quality of fuel, the price of fuel, location of the petrol complex, loyalty programs offered by petrol complexes, offered services, additional services and promotions. The detailed structure of petrol market of Ukraine is presented, where 68 % of fueling market controls ten companies, namely the group of companies Privat, which is represented on the market under such brands as Avias, Ukrtatnafta, ANP, Maveks, Sentosa Oil, Yukon and others, WOG, OKKO, AMIS, BRSM-Nafta, Shell, TNK, SunOil, Market, Tarnett. The second largest participant at the fueling market of Ukraine is a network of Ukrnafta, which belongs to the state company “Naftogaz Ukraine”. Its share is 32 % of all petrol stations` market and it is represented by such brands as: ANP, AVIS, Ukrnafta, Sentora, Maveks and others. The dependence of a petrol quality from the source of origin is analyzed, despite the fact that the fuel at the petrol complexes in Ukraine comes both from Ukraine and abroad. Domestic refineries have high project capacity and optimal territorial location, but the volumes of refining annually fall. This leads to increasing supplies from abroad, namely Russia, Belarus, Greece, Poland, Lithuania, Israel, Romania and Bulgaria. The price of petrol, in particular A-95, in the Lviv region in 2011–2016 is considered, and determined that the maximum rates in UAH equivalent of all grades of petrol were installed in early February 2015. However, given the exchange rate of the euro, there were two peak periods: the first in June and July 2012, when prices were highest at the A-95, A-98 and LPG (gas); second in March 2015 for A-92 and diesel fuel. The quantitative location of petrol stations in all regions of Ukraine as well as their geographic concentration is presented. The structure of the services offered by filling complexes is presented; this structure is formed of four elements: the root of the services – the basic petrol station that offers only refiling, additional paid services, auxiliary paid services and useful free services.
Analysis of criteria that predetermine the choice of filling complexes
Keywords: автозаправний комплекс; мережа автозаправних комплексів; паливо; критерії; якість; ціна; petrol station; network of petrol stations; fuel; criteria; quality; price